You don't need a lottery to do your duty - Abd Razak, Dzulkifli (2007)
IT had all the ingredients of a colourful fireworks display that could have kept the nation entertained for a long time. But this was not the case, when the "MyKad lucky draw" — Jom Tukar dan Menang — became a non-event. To some it was an anticlimax, given how the report was initially framed. Although the issue was played up when one menteri besar joined in the fray and chose to rap the Home Affairs Minister for making the allegedly "silly and rubbish" remark, fortunately it fizzled off quickly. The person directly implicated, the former Home Affairs Minister, was bold enough to come forward to clear the air and took a sharply different stance. This is not about the merit or otherwise of the lucky draw, rather it is about how a potentially explosive issue can be defused with humility and moral courage.